Peran penting pendidikan bahasa Arab di era digital - Auliya, Rizka (Maliki Interdisciplinary Journal, 2024)
In the 4.0 era, there are lots of media used for learning media, with this learning media it really helps an educator in delivering material to students, the use of this digitalization era really helps students and teachers in the teaching and learning process, especially in teaching Arabic to students. learners. Arabic itself is a language that is rarely studied and has become the official language after English. With the media in the form of increasingly sophisticated tools, learning can be made easier and accessible everywhere. In this research, we use literature studies by only looking at the development of several similar discussions on social media. With this research, the aim is to see how the progress provided by increasingly advanced digitalization can have a positive or negative impact.